Motivations to Enroll in Education Graduate Programs in Jordan: A Qualitative Field Study at Yarmouk University - Mohammad Farhan A. Alqudah; Mohammad Ali M. Asiri (University of Science and Technology, Yemen, 2017)
The present study aimed to identify the causes and motives of Yarmouk University students to enroll in graduate programs of educational disciplines in Jordan. Ten students (6 males and 4 females) participated in the study. The study used qualitative research method by means of in-depth interviews during which the participants were given various open questions in each session so as to express their views about the issue under investigation. After the analysis of participants' responses, it was found that they focused on the following motives: career advancement; creation of wider job opportunities; social motivation, which focuses on improving the social status; formation of social relationships; friends and family's encouragement to pursue graduate studies. Then economic motives were brought in by the participants, who believed that to get a graduate degree would increase their income, career promotion, personal living standards, and job opportunities abroad. The results also pointed to the role of psychological motivation for admission to the College of Graduate Studies. This would provide psychological stability and satisfaction, and self-esteem. There was also a reference to the admission policies at universities which became more flexible than before, whereby standards have also changed. This made admission more open than before, which encouraged more students to apply to graduate programs. They also added that in view of these standards and policies, it is clear that more students will apply to the graduate programs in the future; and other new disciplines would be opened in the future as well. Keywords: Motivations of enrollment, Graduate studies, Programs, Educational disciplines, Qualitative study, Yarmouk University, Jordan.